Planet Jawi: Mastering Jawi Through Gamified Assessment - Mat Zain, Nurul Hidayah; Mohamed Noh, Nor Azida; Mohd Yasin, Anita; Ismail, Ismassabah; Yahizan, Siti Nurkhairina (2020)
Jawi is an art of writing that originated from the Arabic writing system, which is Arab letters infused into the Malay writing system. Nowadays, the lack of use of Jawi and the assumption that Jawi is challenging to learn to cause the young generation now slowly to forget Jawi and deny this language. Based on the preliminary study conducted, most of the student agrees that Jawi is a crucial subject and student strongly agree that they did not enjoy learning Jawi through a traditional method such as a textbook. Hence, this project develops an application, namely Planet Jawi, to learn Jawi through gamification. The target audience for this application is students ages seven to nine years old. This project implemented Rapid Application Development (RAD) as a method to design and develop Planet Jawi. The application involved three topics about Jawi such as basic Jawi Alphabet, which comprises 37 Alphabet, ‘Huruf Jawi tidak Bersambung’, and ‘Padan Huruf’ which cover ‘Huruf Vokal’ topics. For the future works of Planet Jawi application, the use of a variety of languages such as English can enhance to attract more users and variety the content covered in Jawi